Dystocia Caused by Uterine Torsion and Surgical Intervention by Cesarean Section in She-Camel (Case Report) - Abdulbari Alfaris; Hussein Khamees; Taher Fahid (Basrah Journal of Veterinary Research)
This case was recorded in Basra province, southern Iraq, in February 2018. A case of a pregnant camel was reported in the last days of pregnancy, according to the owner of the animal and the date of the case. As soon as the case was received at the veterinary consulting clinic at the College of Veterinary Medicine - University of Basra, the camel was suffering from labor contractions for two days, without the appearance of fetal fluids or a fetal sac (water bag). The animal was manually examined vaginally, and it was found that there was a twisting of the uterus (uterine torsion) in a counterclockwise direction of 180 degrees. The decision was made by the specialists that a cesarean section should be performed. A cesarean section was performed and a dead fetus was extracted. The necessary dealings were taken after the operation and instructions were given to the owner to take care of the animal and to complete the required treatments.